Arahan Perencanaan Jalur Pedestrian di Pusat Kota Makassar Berbasis Kinerja Tingkat Pelayanan dan Persepsi Pejalan Kaki - Yushalihah Fitri Taufik; Arifuddin Akil; Mimi Arifin (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2018)
Roads located in the central area of ​​Makassar City such as Jl. Ahmad Yani, Jend. Sudirman, Gunung Bulusaraung and Hos Cokroaminoto are fairly crowded centers of activity. Visually, the pedestrian lane on the road section has not met the expectations of its users. Therefore, it is necessary to evaluate the quality and performance to achieve optimal planning. This study aims to determine the quality and performance of pedestrian lines in the central area of ​​Makassar City. Data collection methods used are, observation, questionnaire, documentation and literature study. The analytical method used is the analysis of Level of Service (LOS) and Importance Performance Analysis (IPA). The results of this study are that the pedestrian path in the study area in general does not meet the pedestrian path planning standards. The level of pedestrian service in general is on Jl. Ahmad Yani and Jend. Sudirman is classified as LOS A, on Jl. G. Bulusaraung is classified as LOS E and Jl. Hos Cokroaminoto has no pedestrian path. Based on the perception of the level of satisfaction of pedestrians, Jalan Ahmad Yani and Jl. Jend. Sudirman is classified as high, while on Jl. Mount Bulusaraung and Hos Cokroaminoto are classified as lacking.